Causative Agents in Patients Presenting with Acute Viral Hepatitis along with their Clinical Profile at a Tertiary Care Hospital, Western U.P. (Academia Journal of Medicine, 2024)
Acute viral hepatitis (AVH) is a common health-related problem throughout the world, but morbidity and mortality are prevalently seen in developing countries like India. In India, AVH is most commonly caused by HAV (hepatitis A virus) and HEV (hepatitis E virus) and in few cases, HBV (Hepatitis B virus) is the etiological agent. HEV mainly affects the middle-aged population, is mild in symptoms however it is lethal with 30% mortality in pregnant females compared to the mortality of ≤1% in the general population. This study was focussed to identify the etiological agents, various clinical - laboratory factors, disease severity and associated complications in patients presenting with AVH. In our study, HEV was the most common etiological agent accounting for 43.6% of cases followed by HAV (29.1%), HBV (26.1%) and HCV (1.2%). The most common age group involved with AVH was the adult group i.e. from 21-30 yrs (35.1%) followed by 11-20 yrs (27.9%), below 10 yrs (15.1%) and 31-40 yrs (14.5%). The commonest symptom was yellow-colored urine (86.1%) followed by yellow discolouration of sclera and loss of appetite. Bleeding derangement was observed in all patients with acute liver failure (ALF) while Hepatic encephalopathy was observed in 3 patients with ALF. To conclude, integration of diagnostic measures, early diagnosis, treatment protocols, prevention and mass vaccination will help in the overall reduction of AVH cases and related complications.
Keywords: Acute viral hepatitis,; acute liver failure; Anti -HEV